2006
DOI: 10.1002/ajmg.b.30428
|View full text |Cite
|
Sign up to set email alerts
|

A promoter polymorphism (−839 C > T) at the dopamine transporter gene is associated with attention deficit/hyperactivity disorder in Brazilian children

Abstract: The dopamine transporter (DAT) plays a key role in the regulation of dopaminergic neurotransmission and is also the major site of action for methylphenidate which is one of the main drugs used to treat attention deficit hyperactivity disorder (ADHD). Most association studies with ADHD have concentrated on the 3'-untranslated region of the gene (3'-UTR) mainly in a variable number of tandem repeat (VNTR) polymorphism, but these investigations have reported discordant results. In this study, we tested this VNTR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 58 publications
1
14
1
Order By: Relevance
“…another study found an association with a polymorphism further upstream (rs2652511) with ADHD in a Brazilian sample [14].…”
Section: Page 8 Of 11mentioning
confidence: 86%
See 1 more Smart Citation
“…another study found an association with a polymorphism further upstream (rs2652511) with ADHD in a Brazilian sample [14].…”
Section: Page 8 Of 11mentioning
confidence: 86%
“…A c c e p t e d M a n u s c r i p t region of the DAT1 gene with two further SNP markers [14,21]. In 2006, it was reported that a SNP polymorphism located 67bp upstream to the translation start site was associated with ADHD in a small Iranian population [21].…”
Section: Page 8 Of 11mentioning
confidence: 99%
“…The negative result with this polymorphism was replicated by Genro et al with 243 children and adolescents and their parents; however, these authors observed, on family-based analyses, that the C allele from the -839 C > T polymorphism at the DAT1 gene was overtransmitted to ADHD children. 55 Genro et al also showed that the absence of association between DRD4 and DAT1 VNTRs polymorphisms with ADHD was not due to IQ variability. 56 Roman et al, using family-based association analyses of a DBH TaqI polymorphism, showed a preferential transmission of the A2 allele to ADHD children and adolescents.…”
Section: Research Groups and Their Main Findings In The Brazilian Popmentioning
confidence: 98%
“…For the 3ЈUTR VNTR, independent data were available from 15 TDT Brookes et al 2006b;Curran et al 2001b;Feng et al 2005b;Galili-Weisstub and Segman 2003;Hebebrand et al 2006;Kim et al 2005b;Kustanovich et al 2004;Lim et al 2006;Maher et al 2002;Mick et al unpublished data;Todd et al 2001a;Waldman et al 1998) and 19 Case-Control/HHRR studies (Bakker et al 2005;Banoei et al 2008;Bobb et al 2005;Carrasco et al 2004;Cheuk et al 2006b;Cook et al 1995;Cornish et al 2005;Das and Mukhopadhyay 2007;Genro et al 2007;Hawi et al 2003;Jiang et al 1999;Kim et al 2006b;Kopeckova et al 2008;Langley et al 2005;Qian et al 2004;Simsek et al 2005;Smith et al 2003;Swanson et al 2000b;Wang et al 2008), with the 480-bp (or 10-repeat) allele designated as the "risk" allele. Results of this meta-analysis, shown in Fig.…”
Section: Dopamine Transporter Gene (Dat1)mentioning
confidence: 99%
“…For example, the DAT1 polymorphisms that were meta-analyzed in the present review are located in the middle to 3Ј end of the gene, but it is notable that several studies have also reported signiWcant associations with polymorphisms at the 5Ј end of the gene. For example, two SNPs (rs2550946 and rs11564750) located in the promoter region of DAT1 have shown evidence of association with ADHD in the International Multi-site ADHD Genetics (IMAGE) (Faraone and Asherson 2005) sample (Brookes et al 2006a;Brookes et al 2008), and although they tested for association using diVerent sets of SNPs, two additional studies have reported signiWcant associations with SNPs in the 5Ј region Genro et al 2007). Given that there is little evidence of linkage disequilibrium between polymorphisms at the 5Ј and 3Ј ends of DAT1 (Greenwood et al 2002), these results, in addition to those of the present review, suggest that there may be multiple functional variants within DAT1 that confer risk for ADHD.…”
Section: Dopamine Transporter Gene (Dat1)mentioning
confidence: 99%